The effect of vibration on kinematics and muscle activation during cycling - Viellehner, J.; Potthast, W. (Journal of Sports Sciences, 2022)
Vibration has the potential to compromise performance in cycling. This study aimed to investigate the effects of vibration on full-body kinematics and muscle activation time series. Nineteen male amateur cyclists (mass 74.9 ± 5.9 kg, body height 1.82 ± 0.05 m, Vo2max 57 ± 9 ml/kg/min, age 27 ± 7 years) cycled (216 ± 16 W) with (Vib) and without (NoVib) vibration. Full-body kinematics and muscle activation time series were analysed. Vibration did not affect lower extremity joint kinematics significantly. The pelvic rotated with vibration towards the posterior direction (NoVib: 22.2 ± 4.8°, Vib: 23.1 ± 4.7°, p = 0.016, d = 0.20), upper body lean (NoVib: 157.8 ± 3.0°, Vib: 158.9 ± 3.4°, p = 0.001, d = 0.35) and elbow flexion (NoVib: 27.0 ± 8.2°, Vib: 29.4 ± 9.0°, p = 0.010, d = 0.28) increased significantly with vibration. The activation of lower extremity muscles (soleus, gastrocnemius lat., tibialis ant., vastus med., rectus fem., biceps fem.) increased significantly during varying phases of the crank cycle due to vibration. Vibration increased arm and shoulder muscle (triceps brachii, deltoideus pars scapularis) activation significantly over almost the entire crank cycle. The co-contraction of knee and ankle flexors and extensors (vastus med. - gastrocnemius lat., vastus med. - biceps fem., soleus - tibialis ant.) increased significantly with vibration. In conclusion vibrations influence main tasks such as propulsion and upper body stabilization on the bicycle to a different extent. The effect of vibration on the task of propulsion is limited due to unchanged lower body kinematics and only phase-specific increases of muscular activation during the crank cycle. Additional demands on upper body stabilization are indicated by adjusted upper body kinematics and increased muscle activation of the arm and shoulder muscles during major parts of the cranking cycle.